Comparison of Sevoflurane Plus Dexmedetomidine Infusion and Dexmedetomidine Infusion to Prevent Awareness During Cardiopulmonary Bypass Surgery - Adnan Akram, Muhammad; Alam, Waqas; Masroor, Rehan; Raza Ali Shah, Syed Ali; Bashir Malik, Imran; Ali Memon, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To find out the frequency of intra-operative awareness and to compare the effect of Sevoflurane plus Dexmedetomidine with only Dexmedetomidine infusion in preventing awareness during cardiopulmonary bypass surgery. Study Design: Quasi-experimental study. Place and Duration of Study: Adult Cardiac Surgery and Anesthesiology department, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from May to Nov 2023. Methodology: Eighty patients who underwent elective cardiac surgery (valvular and CABG) on Cardiopulmonary Bypass under general anesthesia irrespective of age and gender were recruited through non-probability consecutive sampling with non-random allocation of study participants. Patients were divided into S Group (Sevoflurane plus Dexmedetomidine Group) and D Group (Dexmedetomidine Group). Modified Brice questionnaire was used to assess awareness after 24 hours of surgery. Chi-square and t-test were applied to compare the study variables among study groups. p <0.05 was considered as statistically significant. Results: A total of 80 patients, who underwent cardiac surgery were recruited. Out of which 40(50.0%) were included in S group and 40(50.0%) were included in D group. 67(83.7%) were males and 13(16.3%) were females. Mean age of the study participants was 59.98±6.85 years. Comparison of study groups showed that 4(10.0%) patients from group-D and 3(7.50%) patients of group-S experienced awareness during surgery (p=1.00). Mean Cardiopulmonary Bypass time was significantly different among study groups (p=0.02) Conclusion: Patients in S-group experienced slightly less awareness as compared to the patients in D-group but the difference was not statistically significant concluding the fact that Dexmedetomidine is sufficient to avoid awareness